2018
DOI: 10.1038/s41428-018-0143-6
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-SAXS observation of fibril-sized structure formation after the necking of poly(ethylene terephthalate) and poly(phenylene sulfide) fibers

Abstract: Ultra-SAXS observation of fibril-size structure formation after the necking of poly(ethylene terephthalate) and poly(phenylene sulfide

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The three‐phase model probably with minor differences is not rejected by new advanced analytical techniques 39–42 and the idea of the presence of oriented amorphous (amorphous with correlation) and non‐oriented amorphous domains in PET drawn filaments have found more support. It is clearly stated that the classical two‐phase model of crystal and amorphous phases were unable to correlate structure and properties and it was found that there must be a third phase, an oriented, intermediate phase, located mainly between the fibrils 39 .…”
Section: General Aspectsmentioning
confidence: 99%
See 3 more Smart Citations
“…The three‐phase model probably with minor differences is not rejected by new advanced analytical techniques 39–42 and the idea of the presence of oriented amorphous (amorphous with correlation) and non‐oriented amorphous domains in PET drawn filaments have found more support. It is clearly stated that the classical two‐phase model of crystal and amorphous phases were unable to correlate structure and properties and it was found that there must be a third phase, an oriented, intermediate phase, located mainly between the fibrils 39 .…”
Section: General Aspectsmentioning
confidence: 99%
“…It is clearly stated that the classical two‐phase model of crystal and amorphous phases were unable to correlate structure and properties and it was found that there must be a third phase, an oriented, intermediate phase, located mainly between the fibrils 39 . The formation of fibril‐sized structures with high density fluctuation after necking using ultra‐small‐angle X‐ray scattering was observed 40 . The development of both the mesophase and the crystalline structure was considered.…”
Section: General Aspectsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this experimental geometry, we often face the serious problem that the reflection of incident X-rays interferes with the 2D SAXS patterns near the sample edge, which can result in anomalous scattering (artifacts) and seriously damage the reconstructed CT image. Voids within samples also cause strong scattering (Nozue et al, 2007;Yang et al, 1997;Etrillard et al, 2005;Grubb & Murthy, 2010;Tomisawa et al, 2019) which interferes with the accuracy of the reconstructed CT image. We can avoid the appearance of artifacts in CT images by analyzing the intensities at q positions outside these streaks or by changing the measurement conditions, such as the camera length.…”
Section: Introductionmentioning
confidence: 99%